2013
DOI: 10.15381/rivep.v24i2.2493
|View full text |Cite
|
Sign up to set email alerts
|

Tasa De Ovulación Utilizando Liberador De Gonadotropinas Y Plasma Seminal en Alpacas Y Llamas

Abstract: RESUMENSe trabajó con 93 alpacas y 92 llamas a fin de determinar el porcentaje de ovulación utilizando GnRH (buserelina) y plasma seminal de alpaca como inductor de ovulación en alpacas y llamas. Los animales se distribuyeron en dos grupos, un grupo tratado con 42 µg de buserelina intramuscular y otro grupo tratado con 1 ml de plasma seminal intramuscular (50/50% de plasma seminal y PBS + antibióticos). La tasa de ovulación fue de 78.7 y 88.9% en alpacas y 80.6 y 70.0 en llamas con buserelina y plasma seminal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…In B-mode ultrasonography of the CL in recipient llamas show morphometric characteristics such as area, volume and diameter highly related to studies on follicular dynamics in llamas specifically with sizes of donor follicles reaching diameters of 10.0±2.0 mm and 11.8±1.6 mm respectively 3,27 , the maximum follicular diameter is related to the future diameter of the CL since these follicles have active angiogenesis after theca formation, which promotes the permeability of blood vessels, ovulation and subsequent formation of the CL 28 , in cows for meat and milk production, ovulation of a preovulatory follicle of greater diameter leads to a CL of good size; this characteristic seems to be associated with fertility 29,30 . The diameter of the CL of the llamas was 12.7±1.7 mm, compared to other studies, are similar to those reported at 7 days post hormone application reaching diameters of 12.3±0.6 mm, 10.4±0.4 mm, 11±1.9, 11.19±0.32 mm [31][32][33] . While the area of the CL was 0.119±0.03 cm 2 and the volume of the CL evaluated was 0.84±0.34 cm 3 , these being the first results reported with various morphometric measurements of the CL and their correlation between them in llamas by US.…”
Section: Figure 2 Ultrasonographic Evaluation Of the Doppler Characteristics Of The CL Of Recipient Llamas Discussionsupporting
confidence: 89%
“…In B-mode ultrasonography of the CL in recipient llamas show morphometric characteristics such as area, volume and diameter highly related to studies on follicular dynamics in llamas specifically with sizes of donor follicles reaching diameters of 10.0±2.0 mm and 11.8±1.6 mm respectively 3,27 , the maximum follicular diameter is related to the future diameter of the CL since these follicles have active angiogenesis after theca formation, which promotes the permeability of blood vessels, ovulation and subsequent formation of the CL 28 , in cows for meat and milk production, ovulation of a preovulatory follicle of greater diameter leads to a CL of good size; this characteristic seems to be associated with fertility 29,30 . The diameter of the CL of the llamas was 12.7±1.7 mm, compared to other studies, are similar to those reported at 7 days post hormone application reaching diameters of 12.3±0.6 mm, 10.4±0.4 mm, 11±1.9, 11.19±0.32 mm [31][32][33] . While the area of the CL was 0.119±0.03 cm 2 and the volume of the CL evaluated was 0.84±0.34 cm 3 , these being the first results reported with various morphometric measurements of the CL and their correlation between them in llamas by US.…”
Section: Figure 2 Ultrasonographic Evaluation Of the Doppler Characteristics Of The CL Of Recipient Llamas Discussionsupporting
confidence: 89%
“…In B-mode ultrasonography of the CL in recipient llamas show morphometric characteristics such as area, volume and diameter highly related to studies on follicular dynamics in llamas specifically with sizes of donor follicles reaching diameters of 10.0±2.0 mm and 11.8±1.6 mm respectively 3,27 , the maximum follicular diameter is related to the future diameter of the CL since these follicles have active angiogenesis after theca formation, which promotes the permeability of blood vessels, ovulation and subsequent formation of the CL 28 , in cows for meat and milk production, ovulation of a preovulatory follicle of greater diameter leads to a CL of good size; this characteristic seems to be associated with fertility 29,30 . The diameter of the CL of the llamas was 12.7±1.7 mm, compared to other studies, are similar to those reported at 7 days post hormone application reaching diameters of 12.3±0.6 mm, 10.4±0.4 mm, 11±1.9, 11.19±0.32 mm [31][32][33] . While the area of the CL was 0.119±0.03 cm 2 and the volume of the CL evaluated was 0.84±0.34 cm 3 , these being the first results reported with various morphometric measurements of the CL and their correlation between them in llamas by US.…”
Section: Figure 2 Ultrasonographic Evaluation Of the Doppler Characteristics Of The CL Of Recipient Llamas Discussionsupporting
confidence: 89%